E-Identity: Responsibility or Commodity - Seljan, Sanja; Stančić, Hrvoje; Crnec, Dina Salopek, Anita (2007)
The aim of this paper is to analyze importance of e-identity, related issues (e.g. trustworthness of information, pseudonimity, privacy, fraud, property) and role of virutal life in the real one. As Internet users are in great proportion service-oriented and interested in interaction, intermediation and social network communication, the reputation of e-identity has become increasingly important. In this paper two aspects of digital identities are analyzed: encripted identity (e.g. through passwords) and personal virtual identities, used for in forums, chats, blogs, etc. which are created through explicit statements (true or false) of users and by implicit ways of interaction and behaviour. After elaboration on main types of identification and web services, a pilot study on reliability of information of e-identity has been presented made among students of the Faculty of Humanities and Social Sciences. The aim of the paper does not pretend to list detailed issuses but to raise the awarness related to e-identity.
Projekt MZOS
ENG